2023
DOI: 10.3390/ma16041729
|View full text |Cite
|
Sign up to set email alerts
|

Melt Pool Shape Evaluation by Single-Track Experiments and Finite-Element Thermal Analysis: Balling and Lack of Fusion Criteria for Generating Process Window of Inconel738LC

Abstract: Defects occur in laser powder bed fusion (L-PBF) such as the keyholing, lack of fusion, and the balling depending on the laser power (P) and the scan speed (V). The figure shows that the occupied regions of each defect are the process window and are essentially important to fabricate a high-quality part. This paper is a study of process window generation using single-track experiments and finite-element method simulation of thermal conduction for Inconel738LC alloy. A series of single-track experiments were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…As described above, an average particle diameter slightly larger than the thickness of the powder bed is used in some conventionally used L-PBF systems. For example, a thickness of 30 or 50 µm for the powder bed formation region was set for powders with an average particle diameter of 29 µm in [10,40]. In the present study, the ratio between the average diameter (even up to 40 µm) and the powder bed formation region thickness was smaller compared to our previous studies.…”
Section: Equivalency Of Particle Size Distributionmentioning
confidence: 58%
See 2 more Smart Citations
“…As described above, an average particle diameter slightly larger than the thickness of the powder bed is used in some conventionally used L-PBF systems. For example, a thickness of 30 or 50 µm for the powder bed formation region was set for powders with an average particle diameter of 29 µm in [10,40]. In the present study, the ratio between the average diameter (even up to 40 µm) and the powder bed formation region thickness was smaller compared to our previous studies.…”
Section: Equivalency Of Particle Size Distributionmentioning
confidence: 58%
“…The particle size distribution of the Ni-based alloy (Hastelloy X) powder used in this study is shown in Figure 1. The average particle diameter of Hastelloy X powder was 28.9 µm [10,40]. To investigate the effect of particle size within a range similar to that of the Hastelloy X powder used in this study, five different particle size distributions based on Gaussian distributions were used.…”
Section: Powder Spreading Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A procedure for the single-track experiment has been described in detail in the cited Refs. [24]. A brief summary of the experimental procedure is described here.…”
Section: Single-track Experimentsmentioning
confidence: 99%